2013
DOI: 10.1093/glycob/cwt100
|View full text |Cite
|
Sign up to set email alerts
|

Brittlestars contain highly sulfated chondroitin sulfates/dermatan sulfates that promote fibroblast growth factor 2-induced cell signaling

Abstract: Glycosaminoglycans (GAGs) isolated from brittlestars, Echinodermata class Ophiuroidea, were characterized, as part of attempts to understand the evolutionary development of these polysaccharides. A population of chondroitin sulfate/dermatan sulfate (CS/DS) chains with a high overall degree of sulfation and hexuronate epimerization was the major GAG found, whereas heparan sulfate (HS) was below detection level. Enzymatic digestion with different chondroitin lyases revealed exceptionally high proportions of di- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…Furthermore, distinct carbohydrate structures can sometimes fulfil the role of HS/heparin, as has been shown for CS/DS extracted from brittlestars, which activated FGF-2 [85]. However, as was the case for AT, FGF-1 signalling correlated strongly with protein stabilization induced by the polysaccharides, whereas FGF-2 signalling did not [79].…”
Section: Antithrombin-heparin Pentasaccharide: An Exception That Doesmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, distinct carbohydrate structures can sometimes fulfil the role of HS/heparin, as has been shown for CS/DS extracted from brittlestars, which activated FGF-2 [85]. However, as was the case for AT, FGF-1 signalling correlated strongly with protein stabilization induced by the polysaccharides, whereas FGF-2 signalling did not [79].…”
Section: Antithrombin-heparin Pentasaccharide: An Exception That Doesmentioning
confidence: 79%
“…The employment of such a series of modified heparin derivatives, in which sequence diversity has been reduced by systematic desulfation, has also shown that no simple relationship exists between sulfation and charge distribution and their ability to support signalling with FGF-1 and -2 [84,43]. Furthermore, distinct carbohydrate structures can sometimes fulfil the role of HS/heparin, as has been shown for CS/DS extracted from brittlestars, which activated FGF-2 [85]. However, as was the case for AT, FGF-1 signalling correlated strongly with protein stabilization induced by the polysaccharides, whereas FGF-2 signalling did not [79].…”
Section: Heparan Sulfate/heparin Interactions With Fibroblastmentioning
confidence: 99%
“…Our model clearly shows that Fgf2 does not induce proliferation if CS/DS 2-O sulfation is increased on the cell surface despite ERK1/2 activation. Brittle star (class Ophiuroidea) 2-O sulfated CS/DS has a high amount of L-IdoA and is able to activate ERK1/2 in the presence of Fgf2 in CHO cells that lack any GAGs (Ramachandra et al, 2014). An explanation could be the domain organization of GAGs, as shown for HS oligosaccharides and their ability to modulate Fgf2-induced ERK1/2 activation (Jastrebova et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that cell surface CS/DS sulfation is a prerequisite for Fgf2 signaling (Ling et al, 2006;Ramachandra et al, 2014) is supported by the finding that there was a reduced Chondroitin-ACI-lyase-digested highly sulfated CHO-K1 and CHO-K1/Ust CS/DS GAGs were fractioned on a Superdex Peptide column. The column was calibrated with cytochrome C to determine void volume (V 0 ) and glycin to determine total column volume (V t ) (n52).…”
Section: Increased Cs/ds 2-o Sulfation In Cho Cells Affects Proliferamentioning
confidence: 95%
“…[ 214 ] This species synthesizes an N-acetyl transferase (NAT) protein, which is capable of detoxifying glyphosate by acetylating the nitrogen moiety,[ 58 ] and this could explain its overgrowth as being linked to glyphosate contamination. An analysis of the GAGs isolated from brittle stars showed exceptionally high proportions of di- and trisulfated chondroitin sulfate/dermatan sulfate disaccharides,[ 233 ] whose synthesis would be severely impaired by Mn deficiency due to chelation by glyphosate.…”
Section: Chondroitin Sulfate Osteomalacia and Arthritismentioning
confidence: 99%